Understanding the concept of the deep learning approach in using storytelling methods in elementary schools - Susilawati; Yeni Hadianti; Risma Nuriyanti (Jurnal Profesi Pendidikan, 2026)
Deep learning in the educational context emphasizes not only theoretical mastery of learning materials but also meaningful learning that involves experiences and real-life situations. This approach encourages students to think critically and creatively and to solve problems through exploratory and interactive activities, such as storytelling. The storytelling method was chosen because it creates an enjoyable learning atmosphere, increases student participation, and fosters students’ intrinsic motivation. Therefore, teachers need to comprehensively understand the concept of the deep learning approach before implementing it through storytelling. This study aims to explore teachers’ understanding of the deep learning approach in the use of storytelling in elementary schools, as well as the challenges they face in integrating storytelling with deep learning. This study employed a qualitative approach with a case study design, with data collected through interviews and questionnaires. The participants were 10 elementary school teachers in West Java who had at least four years of teaching experience and were civil servants. The results showed that some teachers had a positive understanding of the importance of the deep learning approach. However, several teachers still encountered challenges in implementing this approach effectively, including limited in-depth understanding, difficulty generating story ideas, and challenges in managing students with diverse learning styles. This study suggests the need for continuous teacher training and the development of appropriate story ideas based on students’ learning styles at each grade level.